Differentiation among closely related organisms of the Actinobacillus-Haemophilus-Pasteurella group by means of lysozyme and EDTA. - Olsen, I (1985)
Bacteriolysis in Tris-maleate buffer (0.005 M, pH 7.2) supplemented with EDTA (0.01 M) and hen egg white lysozyme (HEWL, 1.0 microgram/ml) was set up to assist differentiation between the taxonomically closely related Actinobacillus actinomycetemcomitans and Haemophilus aphrophilus. A. actinomycetemcomitans was more sensitive to lysis in this system than H. aphrophilus. The standard method for bacteriolysis separated the 10 tested strains of A. actinomycetemcomitans into two groups (I and II) based on their lysis patterns, whereas the 7 strains of H. aphrophilus examined were homogeneous. In group I of A. actinomycetemcomitans, EDTA displayed a considerable lytic effect, which was not increased by supplementation with HEWL. In group II, the lytic effect of EDTA was much less, but HEWL had a considerable supplementary lytic effect. When the turbidity of A. actinomycetemcomitans (ATCC 29522) or H. aphrophilus (ATCC 33389) suspended in Tris buffer was monitored at close pH intervals (0.2) from pH 5.2 to 9.2, maximal lysis of ATCC 29522 occurred with EDTA at pH 8.0 and with EDTA-HEWL at pH 7.6, while ATCC 33389 lysed with EDTA at pH 9.0 and with EDTA-HEWL at pH 9.2. When other members of the family Pasteurellaceae (Haemophilus influenzae type b, Haemophilus paraphrophilus, Pasteurella multocida, Pasteurella haemolytica, and Pasteurella ureae) were included for comparison, the group I strains of A. actinomycetemcomitans were the most rapidly lysed by EDTA. H. paraphrophilus was the least sensitive of the gram-negative strains tested, but not as resistant as Micrococcus luteus (control). M. luteus was the organism most sensitive to lysozyme, followed by P. ureae and the group II strains of A. actinomycetemcomitans, while the group I strains of A. actinomycetemcomitans, H. paraphrophilus, and P. haemolytica were the least sensitive organisms.